Crystal structure of [(2,4-dichlorobenzyl)triphenylphosphonium] trichloridocopper(II), [C25H20Cl2P]+[CuCl3]− - Ma Chaohong; Dong Xianwu; Jiang Jinke; Jiang Hui (Zeitschrift für Kristallographie - New Crystal Structures)
C25H20Cl5CuP, monoclinic, I2/a (no. 15), a = 16.8258(3) Å, b = 11.0938(2) Å, c = 28.8065(4) Å, β = 106.359(2)°, V = 5159.39(16) Å3, Z = 8, Rgt (F) = 0.0418, wRref (F 2) = 0.1161, T = 293(2) K.